Introduction (EAAE Annual Conference Proceedings, 2023)
We are all overwhelmed with the enormous frequency and power of the many challenges that we are confronted with, in this time called by some the “anthropocene” – the geochronical era in which humans have become one of the most important factors influencing biological, geological, and atmospheric processes on Earth. Climate change continuing – it seems – unhindered, the Corona pandemic not yet fully overcome (and new pandemics possibly at the doorstep), biodiversity endangered, war and natural disasters, uncanny developments in artificial intelligence with great significance also for the scientific production of knowledge: all these “wicked problems” require immediate solution and powerful action. That is where we stand: in a sliding, rising, sinking, shaking, moving sociocultural landscape.